PROFESSIONAL VALUES IN HIGHER TECHNICAL EDUCATION - Ana - Maria Toma; Oana Neculai (Journal of Industrial Design and Engineering Graphics, 2019)
Looking at the educational system in Romania, one can easily see that there is a very big difference between what people learn in school and what it is needed in the work field of our society. Considering all this, the present paper proposes an analysis of how professional values are perceived and understood by students who are at the University now, and who will soon face the challenge of finding a job. Finding these values in the beginning of the University studies, the professors can adopt new ways of teaching, in order to help the students, prepare better for their professional life.